Wood anatomy of the arboreal species of Ipomoea (Convolvulaceae) - Ceja-Romero, Jacqueline; de la Paz Pérez-Olvera, Carmen (Instituto de Ecología, A.C., 2016)
Wood anatomy of eight species of the series Arborescentes of Ipomoea is described. This group has arboreal or viny habit and white or yellow flowers. The species have a type of cambial variant which consists of concentric rings of xylem, phloem and conjunctive tissue. Taxa have solitary pores or sometimes they are grouped, rounded to elliptical and with medium tangential diameter; vessel elements are short with simple perforated plates, pits are alternate, polygonal. Tyloses are present. Fibre-tracheids have a medium length and diameter, and thin walls. Axial parenchyma is vasicentric although occasionally narrow bands are present. Radial parenchyma is formed by uniseriate to multiseriate rays, heterogeneous. Abundant starch grains and druses are present. Results are consistent with those found in the literature for the group, but there are statistical differences in length and diameter of fibres, height and cell number of uniseriate rays and height and series number of multiseriate rays.